Effects of mid-to-late prepartum feed supplementation in Hanwoo beef cows on their performance, blood metabolites, and the carcass characteristics and metabolites of their neonatal calves - Park, Myung Sun; Shokrollahi, Borhan; Kim, Ui Hyung; Won, Jeong Il; Cho, Soo-Hyun; Jin, Shil; Kang, Sung Sik; Moon, Sung Jin; Um, Kyung-Hwan; Jang, Ki Suk; Kim, Hyoun Ju; Kim, Nam Young; et al. (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the implications of supplementary nutrition during the mid-to-late pregnancy on various parameters in Hanwoo cows and their subsequent neonatal calves. Eight Hanwoo cows in their first parity were divided into two groups. The control group (C, 100%) received 3kg of concentrate and 5kg of rice straw throughout the pregnancy period, while the treatment group (T, 150%) increased their diet during mid-to-late pregnancy. Both performance assessments and blood metabolite analyses were performed for the pregnant cows. Neonatal calves were subjected to morphometric evaluations, blood sampling, and detailed morphometric analyses of carcasses and gastrointestinal components. Performance indices of the cows showed that both Pregnancy Period (PregP) and Body Condition Score (BCS) were significantly improved with supplemental feeding (P<0.05). Improvements in Body Weight (BW) and Feed Conversion Ratio (FCR) were not statistically significant. Blood metabolite analysis for the cows revealed decreased levels of triglycerides in the late phase (TGLate), non-esterified fatty acids (NEFALate), and progesterone (P4Late), with a notable increase in glucose in the late phase (GluLate) levels (P<0.01). In the neonatal calves, anatomical metrics of the gastrointestinal tissues showed increased Omasum Width (OmasWdth) values in the supplemented group (P=0.053). There was significant increase of papillae and villus lengths in the rumen and small intestine (P<0.01 and P<0.05, respectively). Morphometric evaluations displayed longer body lengths (BLnth) and larger chest width (ChestWdth) in the treated calves (P<0.05 and P<0.01, respectively). Carcass characteristics showed no substantial variations between the groups, while blood analysis in the calves revealed decreased GPT levels in the nutritionally supplemented group (P<0.05). The findings indicate that supplementing the diets of Hanwoo cows during mid-to-late pregnancy leads to significant changes in select maternal blood metabolites and influences specific anatomical and morphometric features in neonatal calves, all without significant shifts in carcass attributes.